2019
DOI: 10.1109/ms.2019.2919573
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Classification Using N-Gram Inverse Document Frequency and Automated Machine Learning

Abstract: We propose a sentiment classification method with a general machine learning framework. For feature representation, n-gram IDF is used to extract software-engineeringrelated, dataset-specific, positive, neutral, and negative n-gram expressions. For classifiers, an automated machine learning tool is used. In the comparison using publicly available datasets, our method achieved the highest F1 values in positive and negative sentences on all datasets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 12 publications
(19 reference statements)
0
12
0
1
Order By: Relevance
“…When third experiment was performed using 3W3DT, NB outperforms with second fusion model with high accuracy among all. After that, they compared their best model 3W3DT-NB with already existing model, and proposed model leads with accuracy of 88.36% [44] presented general machine learning method with n -gram IDF feature extraction. After feature extraction, an automated ML tool was used for distribution of data according to sentiments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When third experiment was performed using 3W3DT, NB outperforms with second fusion model with high accuracy among all. After that, they compared their best model 3W3DT-NB with already existing model, and proposed model leads with accuracy of 88.36% [44] presented general machine learning method with n -gram IDF feature extraction. After feature extraction, an automated ML tool was used for distribution of data according to sentiments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a subsequent study, Novielli et al [42] found that unsupervised sentiment tools for SE, such as SentistrengthSE work better than supervised tools when applied in a cross-platform setting. Maipradit et al [36] reported superior performance using n-grams in shallow learning models, like SVM, in multiple datasets. However, it is not clear which value of 𝑛 in the n-grams provided the best result.…”
Section: Studying Sentiments Se Repositories/scenariosmentioning
confidence: 99%
“…In Maipradit et al [13], a group of researchers suggests a method for classifying sentiments with a general framework for machine learning. n-gram IDF has been used in feature generation and selection stage.…”
Section: Related Workmentioning
confidence: 99%